Psychological well-being and postgraduate students’ academic achievement in research methodology at an ODL institution - van der Westhuizen, Sanet (South African Journal of Higher Education, 2016)
The purpose of this study was to determine the degree to which psychological well-being variables (sense of coherence, research self-efficacy, locus of control and hope) could predict the academic achievement of students enrolled for a research methodology module at a postgraduate level in an ODL context, while controlling for the effect of biographical variables (gender, age, culture group, home language and employment status). An availability sample (N=840) of postgraduate students enrolled for a course in research methodology across three years was used. Stepwise linear regression showed that gender, culture group and language predicted 17.6% of the variance in academic achievement in this module. When the psychological well-being variables were added, only research self-efficacy emerged as a statistically significant predictor, adding 1.5% of the variance explained in academic achievement in this research methodology module.